Challenges for the childcare market: The implications of COVID-19 for childcare providers in England - Jo Blanden; Claire Crawford; Elaine Drayton; Christine Farquharson; Megan Jarvie; Gillian Paull (Institute for Fiscal Studies (IFS), 2020)
The closures of childcare providers to most families during the COVID-19 crisis have underlined the importance of access to childcare, both to support paid work and to help shape young children's environment. However, the crisis has had severe consequences for the finances of childcare providers, which were already weak in several parts of the sector going into the crisis. Despite a range of government support programmes, many providers lost income during lockdown. In the medium term, a longer-lasting fall in demand for childcare or an increase in costs related to social distancing could seriously hamper financial sustainability in the sector going forward. In this report, we assess the consequences of the pandemic - and the resulting public health response - for the finances of early years childcare providers. The pandemic has hit demand for childcare hard: during the lockdown, when only vulnerable children and those with key worker parents were able to access childcare, fewer than 250,000 children aged 0 to 4 were attending childcare on a given day, compared to around 1.4 million before the pandemic. Since June, the sector has been allowed to serve all children in England, but even before the summer holidays, take-up peaked at 420,000 children. We summarise the packages of support available to providers to help them cope with the loss of demand during the lockdown and over the next few months, and we model how these have interacted with the loss of income due to the crisis and with providers' pre-existing finances. We also discuss how the changes to providers' finances might affect capacity in the sector, and whether and how the government might intervene to support providers. [...]
Keywords: 330; Kinderbetreuung; Markt; Coronavirus; Finanzierung; England